Role of GRP78 in promoting therapeutic-resistant breast cancer. (August 2015) - Cook, Katherine L; Clarke, Robert
Over 230, 000 new cases of invasive breast cancer are diagnosed annually within the USA. Recurrent breast cancer remains a mostly incurable disease with drug resistance, tumor latency and distant metastases driving breast tumor recurrence and morbidity. Understanding drug resistance is a critical component of combating breast cancer. Recently, the protein chaperone GRP78 and the unfolded protein response were implicated as drivers of drug resistance. Preclinical studies show inhibiting GRP78 can reverse drug resistance. Furthermore, drugs developed to target GRP78 show clinical promise in several ongoing clinical trials.